SOSIALISASI DAN PELATIHAN PENGGUNAAN BAHAN ADITIF PEMANIS PADA MINUMAN KUNYIT ASAM DI SMA AR-ROHMAH MALANG - Purnomo, Yudi; Wahyu Fatmadewi, Ardyaneta; Cahyaningtias, Rima; Rahma Refanana, Salsabila; Mariska, Yunia (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
This community service aims to educate on the use of food additives, especially natural sweeteners in health drinks. This activity was carried out at SMA Ar - Rohmah Putra Malang, involving 31 students. The activity start the delivering of material, demonstration and followed by the practice of making sour turmeric health drinks. The beverages using natural sweetener with two methods. Evaluation was carried out by analyzing the level of knowledge of participants from the pretest and posttest questionnaires. The result showed an increase in student knowledge, about 23 %. The post test score in good category increase 2 times fold compared to pre test. The students indicated the participate in the education and practice of making turmeric tamarind health drinks with natural sweeteners.